On the interaction of elastic waves - Krylovas, Aleksandras; Čiegis, Raimondas (Journal of Civil Engineering and Management, 2003)
The non-linear mathematical model of the interaction of elastic waves is presented. The conditions of possible resonant interaction of periodic waves are described. The method of internal averaging for getting uniformly valid asymptotic expansions is used in both, ie resonant and non-resonant, cases. Results of numerical experiments are presented for the resonant interaction of the elastic waves.First Published Online: 26 Jul 2012